Some endocrine hormones level associated with Chronic myelogenous leukemia patients in Al Anbar governorate - Mohammed, Aysar Mahmood; Mohammed, Mousa Jasim (Journal of Neonatal Surgery, 2025)
Background and Objective: Leukemias are linked to numerous immunological and endocrine alterations. Numerous studies have demonstrated an association between endocrine hormone imbalance and the onset of disease in one or both sexes. Hormonal fluctuations can disrupt the physiological homogeneity of the human body, hence impacting health and the progression of associated disorders. We want to examine the impact of changes in endocrine hormones on the immunological response of persons with leukemia. Materials and Methods: This case-control study enrolled 110 individuals, including 90 patients diagnosed with hematological malignancy, at the Medical City Department/Hematology Center in Baghdad, Iraq, from March to November 2024. Among 90 individuals diagnosed with leukemia, 70 were identified with sever chronic myeloid leukemia (CML1), whereas 20 were classed with moderate chronic myeloid leukemia (CML2) based on the disease duration. The research included 20 healthy participants as controls. Erythropoietin (EPO), homocysteine (THcy), parathyroid hormone (PTH), vitamin B12, vitamin D3, and folate levels were assessed in all individuals using both ELISA and immunofluorescence test methods. Calcitonin (Cal) and ferritin were also measured. Results: The study's findings revealed a substantial increase in calcitonin (Cal) and ferritin levels (P < 0.001) in the experimental group compared to the control group. Serum Parathyroid hormone (PTH) levels were elevated in patients diagnosed with the CML1 and CML2 groups compared to the control group (P = 0.01). Erythropoietin (EPO) levels were significantly higher (P = 0.02) in both the CML1 and CML2 groups. The difference was shown to be statistically significant. Both CML1 and CML2 patients had significantly reduced levels of B12 and VD3 in comparison to the control group (P = 0.01 and 0.02, respectively). For Homocystine and Folate (p = 0.004, 0.001, respectively). he study's findings provide concrete evidence for the influence of hormones on the immune response in the etiology of leukemia.